Interaction of Industrial Enterprises and Banking Sector in the Current Context of Russian Economy - KAMBERDIEVA, Svetlana Sultanovna; MIRZABEKOVA, Marina Yurievna; SHELKUNOVA, Tatiana Georgievna (Journal of Advanced Research in Law and Economics, 2017)
The national economy is a complex system, steeped with various relationships and interactions. The banking sector is one of the core subsystems of the national economy, which accumulates and redistributes financial resources. Russia has mostly resource-based economy. At the same time, the available industrial potential and the current development of industrial enterprises, hindered by limited resources and foreign economic sanctions on the one hand, and actively encouraged by the state authorities towards import substitution, on the other hand, thus, objectively needs effective interaction with the banking system. Exactly these issues are reviewed in the present article.